Hotel Service Quality And Customer Loyalty In Jordanian Hotels: A Case Study Of Marriott Hotels Chain - al-Rousan, Ramzi Mahmoud Refai (2011)
In the ever challenging Jordanian hotel industry, service quality is an extremely important competitive policy to maintain customer support and build a strong customer base. The efforts by hotels to win and retain customer loyalty by providing enhanced quality services is ever evolving and becoming more and more challenging. This study attempts to examine the relationship among tourism service quality, customer satisfaction and customer loyalty in three selected Jordanian hotels which are branches of a five-star hotel chain